2016
DOI: 10.18632/oncotarget.7327
|View full text |Cite
|
Sign up to set email alerts
|

CRP2, a new invadopodia actin bundling factor critically promotes breast cancer cell invasion and metastasis

Abstract: A critical process underlying cancer metastasis is the acquisition by tumor cells of an invasive phenotype. At the subcellular level, invasion is facilitated by actin-rich protrusions termed invadopodia, which direct extracellular matrix (ECM) degradation. Here, we report the identification of a new cytoskeletal component of breast cancer cell invadopodia, namely cysteine-rich protein 2 (CRP2). We found that CRP2 was not or only weakly expressed in epithelial breast cancer cells whereas it was up-regulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 59 publications
9
55
1
Order By: Relevance
“…Increased CSRP2 transcription also promotes migration of breast cancer cells via an actin bundling factor [18]. In our study CSRP2 was found predominantly in the nucleus.…”
Section: Discussionsupporting
confidence: 53%
“…Increased CSRP2 transcription also promotes migration of breast cancer cells via an actin bundling factor [18]. In our study CSRP2 was found predominantly in the nucleus.…”
Section: Discussionsupporting
confidence: 53%
“…Although H19 was reported to repress CDH1 expression via interaction with EZH2 (Luo et al, 2013), our findings of CDH1 regulation by H19 , and by both of H19 targets CDK8 and β-catenin, suggest a different mechanism on CDH1 regulation. CSRP2 is a rarely studied gene (Hoffmann et al, 2016), and in this study we identified its clear association with CRC survival. Interestingly, our unpublished data showed that E2F1 knockdown also dramatically reduces and increases CSRP2 and CDH1 mRNA expression, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…Wounds were done manually using the 9 6‐Well WoundMaker tool and filled with collagen. Invasion into the collagen matrix was followed using the IncuCyte device as previously described . Wound confluence was measured at each time point using the automated image acquisition and processing system IncuCyte.…”
Section: Methodsmentioning
confidence: 99%
“…Invasion into the collagen matrix was followed using the IncuCyte device as previously described. 20 Wound confluence was measured at each time point using the automated image acquisition and processing system IncuCyte. Relative wound density (RWD) was used to quantify wound closure.…”
Section: Collagen Invasion Assaymentioning
confidence: 99%